Empathy, indiscipline and employability: A research essay on the bilingual Masters programme 'Cultural Intelligence and Innovation' at Université de Paris. Issue 4 (August 2020) - Bernard, Catherine; Thornton, Sara
This study considers the 2-year bilingual Masters programme, 'Cultural Intelligence and Innovation' at Université de Paris, for which classes are taught in English and in French. Alumni are working as strategic planners, brand managers, community managers, advertisers, futures and trend specialists, web content writers and project leads in a wide variety of organizations throughout the world. This humanities-driven programme has empathy and sensibility at its heart, firstly through the exercise of the imagination and multilingualism and the attendant ability to identify with others, and, secondly, by being attuned to society's faint frequencies allowing cultural foresight. The programme encourages work outside the confines of discipline as well as critique and counter-thinking. Thinking culture and industry together (academic teachers join forces with those from industry to create hybrid content for courses) is important in preparing the students for work. The programme also fosters the ability to detect shifts in sensibility as a first step in innovation. Finally, the authors consider how the programme might be generalized and similar initiatives established in other higher education institutions.